PRACTICAL USE OF THE MODEL FOR EVALUATING CHANGES IN THE PARAMETERS OF THE OPTICAL FIBER DATA TRANSMISSION MEDIUM - Pogrebniak, Liudmyla; Romanenko, Mariia; Bolotiuk, Yuliia (Ukrainian Information Security Research Journal, 2023)
Today, several physical media are used to transmit information between network components based on embedded software, namely: radio channel, fiber optic, and wire lines. The paper considers the possibility of changing the main parameters of the optical fiber line from the time of operation. At the same time, it is considered that the operating conditions of these lines correspond to the conditions established by the manufacturers. In the process of operation, optical fiber information transmission lines are exposed to various external influences (heating, cooling, solar radiation, mechanical and electrical load). The permissible degree of these influences is determined by technical and operational documentation and depends on the design of optical fiber products, climatic performance, method, installation and laying. The parameters used for evaluation can be: operational (measured by standard devices without decommissioning the equipment); technical condition parameters (measured by external equipment with equipment stop, partial or complete disassembly). On the basis of the analysis of existing methods of assessing changes in the main parameters of optical fiber lines over time, one of the methods for solving the problems of technical diagnostics of networks with built-in software is considered in depth. In their works, the authors consider a non-contact induction method of technical diagnostics for a control object in the form of a software-hardware complex based on the energy-time parameter of diagnostics. This parameter allows, without interfering with the system, to measure and quantify the internal physico-chemical aging processes of the component parts of the control object. The proposed approaches can be used, including, to control the physical integrity of the object of control.